The sea of monsters - Riordan, Rick. (Riordan, Rick. Percy Jackson & the Olympians ;, 2006)
Demi-god Percy Jackson and his friends must journey into the Sea of Monsters to save their camp. But first Percy will discover a secret that makes him wonder whether being claimed as Poseidon's son is an honor or a cruel joke.